The Effect of Time-Restricted Eating on Insulin Levels and Insulin Sensitivity in Patients with Polycystic Ovarian Syndrome: A Systematic Review - R. Floyd; R. Gryson; D. Mockler; J. Gibney; S. N. Duggan; L. A. Behan (International Journal of Endocrinology)
Background & Objective. Polycystic ovarian syndrome (PCOS) is the most common reproductive endocrinopathy in women of reproductive age with many associated metabolic symptoms, in particular hyperinsulinemia, insulin resistance, and a high lifetime risk of type 2 diabetes mellitus. The effects of time-restricted eating on metabolic profiles have been investigated in many endocrinopathies, but there is minimal data for PCOS. Here we explore the potential role of time-restricted eating in the nonpharmacological management of PCOS. Designs & Methods. Medline, CINAHL, EMBASE, Web of Science, and Cochrane Library were searched for controlled trials of effects of time-restricted eating regimens on insulin levels in patients with PCOS. A further narrative discussion on the time-restricted eating in PCOS was conducted. Results. 2662 papers were identified with 37 selected for full-text review and one paper meeting criteria for inclusion. Ramadan fasting was the only time-restricted eating regimen trialled in this population with no strong evidence of a significant effect on insulin levels. Conclusion. As the systematic review retrieved only one study investigating time-restricted eating to reduce insulin in patients with PCOS, there is no evidence to suggest that this intervention is effective. From the narrative review, based on studies in other patient groups, time-restricted eating could improve insulin resistance in those with PCOS; however, well-designed studies are required before this intervention can be recommended.